Role-Play As A Method To Overcome Students’ Anxiety In Speaking Skill - Toyib, Ahmat Rondi; Syafi’i, Ahmad (Efektor, 2018)
English Language becomes one of compulsory subject and tested on National Examination. Then, students are expected to not only pass the National Examination but also can master skills in learning English. The most difficult skill to be mastered is speaking. It caused of the lack of motivation from students, the inappropriate method used by the teacher, and the use of media. In other reason, students are rarely given time to practice. It makes them feel anxiety when they are speaking. To overcome that problem teacher can use role-play method in order to overcome students’ anxiety in speaking skill. Through this method, students are fully involved in the activity and have chance to speak with their friends.